Spatio-temporal parameters and lower-limb kinematics of turning gait in typically developing children. - Dixon, P; Stebbins, J; Theologis, T; Zavatsky, A (2013)
Turning is a requirement for most locomotor tasks; however, knowledge of the biomechanical requirements of successful turning is limited. Therefore, the aims of this study were to investigate the spatio-temporal and lower-limb kinematics of 90° turning. Seventeen typically developing children, fitted with full body and multi-segment foot marker sets, having performed both step (outside leg) and spin (inside leg) turning strategies at self-selected velocity, were included in the study. Three turning phases were identified: approach, turn, and depart. Stride velocity and stride length were reduced for both turning strategies for all turning phases (p<0.03 and p<0.01, respectively), while stance time and stride width were increased during only select phases (p<0.05 and p<0.01, respectively) for both turn conditions compared to straight gait. Many spatio-temporal differences between turn conditions and phases were also found (p<0.03). Lower-limb kinematics revealed numerous significant differences mainly in the coronal and transverse planes for the hip, knee, ankle, midfoot, and hallux between conditions (p<0.05). The findings summarized in this study help explain how typically developing children successfully execute turns and provide greater insight into the biomechanics of turning. This knowledge may be applied to a clinical setting to help improve the management of gait disorders in pathological populations, such as children with cerebral palsy.